Endothelium-derived Nitric Oxide Decreases Polymorphonuclear Leukocyte Interaction with the Deeply Injured Arterial Wall under Intermediate and High Shear Conditions - Provost, Patrick; Merhi, Yahye (Thrombosis and Haemostasis, 1997)
Previous studies have shown that nitric oxide (NO) inhibits specific agonist-induced polymorphonuclear leukocyte (neutrophil) and platelet aggregation in vitro. However, the inhibitory effects of NO on neutrophil interaction with the deeply injured arterial wall under conditions of flow is unknown. Therefore, we investigated the influence of NO derived from the endothelium on neutrophil and platelet interactions with the downstream arterial media under controlled flow conditions. Porcine aortic media, simulating deep arterial wall injury, was exposed to flowing porcine non-anticoagulated arterial blood for 5 min at intermediate (1006 s1) and high (3397 s1) shear conditions, and deposition of radiolabeled neutrophils and platelets was quantified. Neutrophil deposition on the exposed arterial media was reduced, by more than 30%, by pretreatment of the endothelium with the physiological precursor of NO, L-arginine, from 84.1 ± 13.7 to 57.4 ± 7.2 X 103/cm2 (p < 0.05) at 1006 s*1, and from 99.3 ± 9.8 to 65.5 ± 8.7 X KP/cm2 (p < 0.05) at 3397 s1 of shear rate, relative to control. Pretreatment of the endothelium with the inactive stereoisomer D-arginine had no effect on neutrophil deposition. These specific inhibitory effects of L-arginine were completely abolished by the inhibitor of NO synthesis, N^-nitro- L-arginine methyl ester (l-NAME) at both shear rates. Endothelial pretreatment with D-arginine, or with L-arginine, in the absence or presence of l-NAME, did not significantly influence platelet interaction with the thrombogenic arterial media at intermediate and high shear rates. These results indicate that NO derived from the endothelium can modulate and has a greater influence on neutrophil, than on platelet, interaction with the injured arterial wall exposing the media under conditions of flow typical to moderately and severely stenosed arteries.